Cover Image, Volume 58, Issue 9. Issue 9 (13th August 2019) - Sammons, Rachel M.; Ghose, Ranajeet; Tsai, Kenneth Y.; Dalby, Kevin N.
Abstract : Cover Caption : The cover image is based on the In Perspective Targeting ERK beyond the boundaries of the kinase active site in melanoma by Rachel M. Sammons et al., DOI10.1002/mc.23047 .